A primitive neuroectodermal tumor in an adult: Case report of a unique location and MRI characteristics. Issue 7 (February 2018) - He, Xin; Chen, Zhongping; Dong, Yutong; Tong, Dan
Abstract: Rationale: Central nervous system primitive neuroectodermal tumors (CNS PNETs) mostly occur in children and present as cerebellar medulloblastoma. A few cases of PNETs occur in the cerebral hemisphere. The presence of a PNET in ventricles is extremely rare. The prognosis of CNS PNET is extremely poor, and the 5-year survival rate does not exceed 35%. In the present study, we describe the first case of a PNET in the ventricles with good prognosis. Patient concerns: The case of a 36-year-old man is reported, who presented with a progressively worsening headache for 2 months. Diagnoses: Magnetic resonance imaging (MRI) revealed multiple tubercula on the walls of the lateral and third ventricles. Histopathologic analysis revealed a hypercellular tumor with small round cells containing hyperchromatic nuclei and a high nucleus:cytoplasm ratio. The analysis was consistent with PNET. Interventions: Radiation therapy covering the entire craniospinal axis was administered, with Temozolomide for synchronous auxiliary treatment. Outcomes: The patient was follow-up for a year and showed no signs of recurrence. Lessons: We present the first CNS PNET located in the ventricles with good prognosis. In this case, radiotherapy with Temozolomide auxiliary treatment presented good efficacy and safety to treat PNET. Additional studies on biomarkers may be useful in predicting personalized therapeutic response.